Computer aided design algorithm for singly fed circularly polarized rectangular microstrip patch antennas - Lumini, Feliciano; Cividanes, Lucio; da S. Lacava, J. C. (International journal of RF and microwave computer-aided engineering, 1999)
Based on a resonant cavity model, this work presents an effective computer aided design (CAD) algorithm to design singly fed circularly polarized (CP) rectangular microstrip patch antennas. The CAD algorithm allows precise prediction of the antenna performance. The analysis of radiation pattern, input impedance, and axial ratio parameters confirm the success of the design. The experimental results from a manufactured prototype operating at 2.25 GHz are in good agreement with the CAD predictions. ©1999 John Wiley & Sons, Inc. Int J RF and Microwave CAE 9: 32–41, 1999.